Analisis Ruang dan Tempat dalam Perspektif Epistemologi Geografi sebagai Ilmu Pengetahuan - Sabihi, Aprianto; Jepril, Jepril; Hasim, Hasim; Nurfaika, Nurfaika (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Geography is a scientific discipline that is very complex in its scope of study. One of the fundamental aspects of geography is the concept of space and place. In the perspective of geographic epistemology, there is a challenge to understand how space and place are interpreted and applied in the context of scientific studies. The aim of this research is to understand space and place from the epistemological perspective of geography as a science. This research uses a literature study method. The results of this research provide a deeper understanding of the dynamic and complex nature of space and place, which is no longer seen as a purely physical entity, but also as a social, cultural, political and economic construction.